Peningkatan Hasil Belajar Siswa Pada Elemen Bhinneka Tunggal Ika Menggunakan Model Cooperative Tipe Think Pair Share di Kelas V SDN 14 Koto Lalang Kota Padang - Yuanda, Masri; Anita, Yesi; Ladiva, Hasmai Bungsu; Meizatri, Ranti (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe the improvement of student learning outcomes in the elements of Bhinneka Tunggal Ika through the implementation of the Think Pair Share cooperative learning model in grade V of SDN 14 Koto Lalang, Padang City. The study used a Classroom Action Research (CAR) approach with qualitative and quantitative methods implemented in two cycles. Cycle I consisted of two meetings, while cycle II was implemented in one meeting. The subjects of the study were teachers as researchers and 28 grade V students consisting of 16 male students and 12 female students. Data collection techniques included observation, tests, and documentation. Observations were used to assess learning planning and implementation, tests were used to measure student learning outcomes, and documentation was used as supporting data. Data analysis was carried out qualitatively through reduction, presentation, and drawing conclusions, and quantitatively by calculating the percentage of indicator achievement in each cycle. The results showed an improvement in learning planning, teacher activities, and student learning outcomes. The average value of student learning outcomes increased from 74.23% in cycle I to 86.35% in cycle II. These findings indicate that the application of the Think Pair Share model is effective in improving student learning outcomes on the Bhinneka Tunggal Ika element in elementary schools